Narration, nation and Mhudi, in the context of a feminine nationalist metaphor and a dream deferred - Mafu, Lucas (Research Journal in Advanced Humanities, 2023)
Sol Plaatje’s Pan-Africanism and a dream of a sub-continent at peace with itself constructed on the principles of ethnic and racial equality comes to a critical paradox with the realisation that it is not possible to achieve it in the face of the political interests of different competing national groups. What ultimately stands out in this novel is the feminine metaphor of African nationalism, which is embedded in Mhudi, the nationalist and cultural icon. This paper traces the narrative voices in the novel Mhudi, in the context of its multi-layered narrations of national histories by different ethnic groups claiming South Africa as their home, and the literary interpretations that arise. Using postclassical narrative theory and historical narratology, this paper considers the possibility of several renderings of Mhudi’s character, South Africa’s history and the contradictory claims to ownership of this land which Plaatje, the nationalist, fictionally presents. In the South Africa of the 1930s, Plaatje’s aspirations of a multicultural, multi-ethnic, and united country which are embodied in Mhudi were deferred. The paper concludes that those aspirations remain deferred even after the end of both colonialism and apartheid.